KRITIK SOSIAL TERHADAP KETIDAKADILAN PADA LIRIK LAGU “BONGKAR” KARYA IWAN FALS - Yuyun Yunengsih; Desma Yuliadi Saputra; Rina Andriani (Indonesian Journal of Thousand Literacies, 2026)
This study aims to identify forms of social criticism that depict injustice, as found in the lyrics of the song "Bongkar" by Iwan Fals. This song was chosen because it contains a profound social message regarding the dynamics of power, oppression, and social inequality that exist in society. This study applies a descriptive qualitative method with a critical discourse analysis approach. The data obtained were then analyzed using Norman Fairclough's theory, discussing the dimensions of text, social practice, and discursiveness. The analysis shows that the lyrics of "Bongkar" depict a critique of social injustice through symbols of resistance, illustrations of oppression by those in power, and a collective call for social change. The lyrics also reflect a view of resistance against the hegemony of power and demonstrate how music plays a role as a means of social criticism and awareness. Therefore, the song "Bongkar" can be seen as a cultural text that functions as a tool for conveying social criticism of structures of injustice within society.